Does Body Perception Shape Visuospatial Perception?. (May 2018) - Legrain, Valéry; Manfron, Louise; Garcia, Marynn; Filbrich, Lieve
How we perceive our body is shaped by sensory experiences with our surrounding environment, as witnessed by poor performance in tasks during which participants judge with their hands crossed the temporal order between two somatosensory stimuli, one applied on each hand. This suggests that somatosensory stimuli are not only processed according to a somatotopic representation but also a spatiotopic representation of the body. We investigated whether the perception of stimuli occurring in external space, such as visual stimuli, can also be influenced by the body posture and somatosensory stimuli. Participants performed temporal order judgements on pairs of visual stimuli, one in each side of space, with their hands uncrossed or crossed. In Experiment 1, participants' hands were placed either near or far from the visual stimuli. In Experiment 2, the visual stimuli were preceded, either by 60 ms or 360 ms, by tactile stimuli applied on the hands placed near the visual stimuli. Manipulating the time interval was intended to activate either a somatotopic or a spatiotopic representation of somatic inputs. We did not obtain any evidence for an influence of body posture on visual temporal order judgment, suggesting that body perception is less relevant for processing extrabody stimuli than the reverse.